Dating Methods of Pleistocene Deposits and Their Problems II. Uranium-Series Disequilibrium Dating - Schwarcz, Henry (Geoscience Canada, 1978)
Abstract U-series dating makes use of the tendency of the short-lived daughters of 238U and 235U to be chemically separated from their parents during sedimentary processes. Ages of samples are determined either from the decay of initial excess of daughter (Daughter Excess, DE, dating) or growth of initially deficient daughter (DD) into secular equilibrium with the parent. DE dating is applicable to marine sediments where initial excesses of "°Th and 23lPa are observed. DD dating is useful on chemically precipitated CaCOa and some biogenic carbonates. By DD dating of travertines associated with various types of geomorphic features, absolute dates for the evolution of land-forms through the Quaternary can be obtained. DD dated speleothems also yield stable isotopic records of past climate.